PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN BALANCED SCORECARD PADA RSUP dr. SOERADJI TIRTONEGORO KLATEN - Ratna S, Mery; Nugroho J, Agung; Julianto SN, Arif (KIAT BISNIS, 2015)
PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN BALANCED SCORECARD PADA RSUP dr. SOERADJI TIRTONEGORO KLATEN Oleh Mery Ratna S, Agung Nugroho J, Arif Julianto SN Fakultas Ekonomi Universitas Widya Dharma Klaten ABSTRACT This research of target (1) knowing influence of applying of good corporate governance and balanced scorecard to performance manajerial, (2) knowing influence of applying of good corporate governance to performance manajerial, (3) knowing influence of applying of balanced scorecard to performance manajerial. Research type is representing of research survey. Population in this research is manager of RSUP dr. Soeradji Tirtonegoro Klaten. Sampel by using saturated sampling technique, where all population member made by sampel. Data type used in this research is quantitative data primary. Analyse the data use analyse the doubled regresi constructively SPSS 16. The result obtained after research is data of sampel manager have normal distribution. Result of examination show is not happened by the multikolinieritas in examinee model. Result of examination show is not happened by the heteroskedastisitas in examinee model. Good Corporate governance and balanced scorecard have an effect on to performance manajerial. Good Corporate governance have an effect on to performance manajerial. Balanced Scorecard do not have an effect on to performance manajerial. internal factors contribution like good corporate governance and balanced scorecard in explaining its influence to performance manajerial only lower that is 26,1% and the rest 73,9% explained by other variable outside this research. Keyword : good corporate governance, balanced scorecard, performance manajerial.